Measuring social support in patients with advanced medical illnesses: An analysis of the Duke–UNC Functional Social Support Questionnaire - SARACINO, REBECCA (Palliat Support Care, 2014)
OBJECTIVE: To date, no measure of social support has been developed specifically for either palliative care or oncology settings. The present study examined the psychometric properties of the Duke–University of North Carolina Functional Social Support Questionnaire (DUFSS) in order to (1) assess the adequacy of the scale in the context of severe medical illness and (2) evaluate whether a brief subset of items might generate roughly comparable utility. METHOD: The 14-item DUFSS was administered to 1,362 individuals with advanced cancer or AIDS. Classical test theory (CTT) and item response theory (IRT) analyses were utilized to develop an abbreviated version of the DUFSS that maintained adequate reliability and validity and might increase the feasibility of its administration in a palliative care setting. The reliability and concurrent validity of the DUFSS-5 were evaluated in a separate validation sample of patients with advanced cancer. RESULTS: Analyses generated a five-item version of the DUFSS (the DUFSS-5) that collapsed response levels into only three options, instead of five. Correlations between the DUFSS-5 and measures of depression, quality of life, and desire for hastened death, as well as regression models testing the main-effect and buffering models of social support, provided support for the utility of the DUFSS-5. SIGNIFICANCE OF RESULTS: Both the DUFSS and the abbreviated DUFSS-5 appear to have adequate reliability and validity in this setting. Moreover, the DUFSS-5 represents a potentially important option for healthcare researchers, particularly for those working in palliative care settings where issues of patient burden are paramount. Such analyses are critical for advancing the development and refinement of psychosocial measures, but have often been neglected.